PENGARUH KONFLIK PERAN GANDA DAN PSYCHOLOGICAL WELL- BEING TERHADAP KINERJA (Studi Pada Perawat Wanita RSUD S.K.Lerik Kota Kupang) - Ummi Rosdiayanti Jalil; Rolland Epafras Fanggidae; Apriana H.J. Fanggidae (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2020)
The purpose of this study is to describe the effect of double role conflict and psychological well-being on the performance of female nurses in S.K.Lerik Public Hospitals Kupang City. Research methodology: The study was conducted with a qualitative approach. Data collection was carried out by filling out the questionnaire by 38 female nurses who were sampled. Data processing is performed by multiple linear regression analysis. Results: The results of this study indicate the influence of dual role conflict variables and psychological well-being on the performance of female nurses in the S.K.Lerik Public Hospital Kupang City both partially and simultaneously. Limitations: This study only discusses the influence of multiple role conflict variables and psychological well-being on the performance of female nurses at the S.K.Lerik Regional Hospital in Kupang. Contribution: This research can be used as scientific information in the field of human resource management..